P39 ATRIAL MASS IN HEART TRANSPLANTED PATIENT WITH CLINICAL HISTORY OF LYMPHOMA. (18th May 2022) - Scirpa, R; Follesa, F; Battistoni, A; Volpe, M
Abstract: Atrial thrombosis is an uncommon complication of cardiac transplant, especially when performed with standard technique. Pathogenetic mechanisms might involve atrial anatomy distortion and abnormalities in its contractile function, which induce flow stasis and thrombus formation, mostly on the surgical suture. A 77–year–old man underwent orthotopic heart transplantation in 2000 for post–ischemic dilated cardiomyopathy. In 2019 he was diagnosed with diffuse large B–cell lymphoma treated with chemotherapy. On March 2021, during follow up period, he had a total body CT scan which showed a submandibular space–occupying lesion, likely as a disease recurrence, and a large atrial mass (30x50 mm). For this reason, he was admitted to the emergency department. Echocardiography documented a massive hyperechogenic formation in an enlarged left atrium. In order to rule out a neoplastic nature, a cardiac CMR was performed, confirming the presence of an oval mass adhering to the posterior left atrial wall with partial involvement of pulmonary veins ostia, with inhomogeneous isointense signal on T1–weighted sequences and hyper–isointense signal on T2–weighted sequences, without significant contrast enhancement, likely representing an endoluminal thrombotic formation. Given the patient's clinical status and his hemodynamic stability, a surgical excision was deferred. The patient was discharged on oral anticoagulant therapy with Warfarin (INR target 2–3). Three months later, a chest CT showed a meaningful mass reduction (11x18mm), which was no longer visible at echocardiography. About 9 months later, complete disappearance of the atrial mass was found at a CT scan. According to scientific literature, differential diagnosis of a newly discovered atrial mass in a transplanted heart includes thrombosis or neoplasia. Thrombosis occurs usually early after surgery, but due to promoting factors, it can arise after many years. The most likely triggering condition is an acquired prothrombotic status: in our case the likely lymphoma recurrence may have led to thrombogenesis. In order to exclude with confidence cardiac metastasis, histological examination would have been necessary. Nevertheless, the meaningful mass reduction, as early as three months after starting oral anticoagulation, and its disappearance nine months after, strongly suggests for atrial thrombosis.